The Impact of Human Resource Management Practices and Corporate Sustainability on Organizational Ethical Climates: An Employee Perspective - Guerci, M. (Journal of business ethics, 2015)
The increasing challenges faced by organizations have led to numerous studies examining human resource management (HRM) practices, organizational ethical climates and sustainability. Despite this, little has been done to explore the possible relationships between these three topics. This study, based on a probabilistic sample of 6,000 employees from six European countries, analyses how HRM practices with the aim of developing organizational ethics influence the benevolent, principled and egoistic ethical climates that exist within organizations, while also investigating the possible moderating role played by their employees’ perception of corporate sustainability. Findings demonstrate that ability-enhancing practices (i.e. recruiting, selection and training) and opportunity-enhancing practices (i.e. job design, industrial relationships and employee involvement) improve benevolent and principled organizational ethical climates, while motivation-enhancing practices (i.e. performance management, compensation and incentives) rather than being related to these organizational ethical climates, are linked to the egoistic climate. In addition, the perceptions of the company’s employees in terms of corporate sustainability moderate these relationships, by reinforcing the positive relationships of ability-enhancing and motivation-enhancing HRM practices in terms of benevolent and principled ethical climates and by reducing the positive relationships between motivation-enhancing practices and egoistic climate. Specific implications for HRM research, teaching and practice are then advanced and discussed.